Porn Star as Brand: Pornification and the Intermedia Career of Rakel Liekki. - Nikunen, Kaarina; Paasonen, Susanna (Velvet Light Trap: A Critical Journal of Film & Television)
This article explores pornification as a reorganization of the cultural position of pornography (porn) through an analysis of the career of Rakel Liekki, a Finnish female porn performer. It states that the porn version of Liekki may be generic which is testified by her motion picture "My Film." It says that Liekki was able to disengage porn from notions of shame and strict norms.